2011
DOI: 10.1039/c0cc02923h
|View full text |Cite
|
Sign up to set email alerts
|

Stability of small mesoporous silicananoparticles in biological media

Abstract: In this work, sub-50 nm pegylated mesoporous silica nanoparticles prepared with hydrothermal treatment are shown to have long-term stability in various media at both room and physiological temperature. Compared to bare mesoporous silica nanoparticles, the highly pegylated mesoporous silica nanoparticles show significantly improved biocompatibility and decreased macrophage uptake, making these nanoparticles viable for in vivo stealth drug delivery applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
164
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(174 citation statements)
references
References 20 publications
8
164
1
1
Order By: Relevance
“…The biocompatibility and biodegradability of PEG has been demonstrated in a number of studies [30,31]. Moreover, the short-and long-term influence of PEGylation on biodegradability of MSNs in different media including aqueous solutions [32], simulated body fluids (SBF) [33], phosphate buffered saline (PBS) [34], and Dulbecco's modified eagle's medium (DMEM) with fetal bovine serum (FBS) [32] has been evaluated. Although the biodegradability of these nanoparticles in complex environments is relatively lower than that in aqueous solutions, however, PEGylation shows an overall enhancing effect on MSN biostability, yielding to a decreased loss of mesoporous parameters such as surface area and pore volume [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocompatibility and biodegradability of PEG has been demonstrated in a number of studies [30,31]. Moreover, the short-and long-term influence of PEGylation on biodegradability of MSNs in different media including aqueous solutions [32], simulated body fluids (SBF) [33], phosphate buffered saline (PBS) [34], and Dulbecco's modified eagle's medium (DMEM) with fetal bovine serum (FBS) [32] has been evaluated. Although the biodegradability of these nanoparticles in complex environments is relatively lower than that in aqueous solutions, however, PEGylation shows an overall enhancing effect on MSN biostability, yielding to a decreased loss of mesoporous parameters such as surface area and pore volume [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the short-and long-term influence of PEGylation on biodegradability of MSNs in different media including aqueous solutions [32], simulated body fluids (SBF) [33], phosphate buffered saline (PBS) [34], and Dulbecco's modified eagle's medium (DMEM) with fetal bovine serum (FBS) [32] has been evaluated. Although the biodegradability of these nanoparticles in complex environments is relatively lower than that in aqueous solutions, however, PEGylation shows an overall enhancing effect on MSN biostability, yielding to a decreased loss of mesoporous parameters such as surface area and pore volume [32,33]. The PEG coating could also improve the colloidal stability of MSNs by increasing their hydrophilicity as well as the steric distances, which in turn reduces the attraction forces between the nanoparticles [14].…”
Section: Discussionmentioning
confidence: 99%
“…13 Further, it was observed that: (i) smaller Stöber silica nanoparticles (24 nm) induce a pronounced hemolytic effect when compared with bigger ones (263 nm); 14 (ii) nanostructures with high aspect ratio (nanorods) are more cytotoxic than spherical nanoparticles; 15 (iii) mesoporous silica nanostructures (MSNs) with ordered pores (MCM-41) induce a stronger hemolytic effect compared with non-ordered; 14 (iv) small mesoporous nanoparticles (20 nm) consisted of ethenylenebridged silsesquioxane present very low toxicity 16 and (v) polymers such as PEG (polyethylene glycol) can be used to coat particles in order to greatly reduce the hemolysis. 17 Furthermore, an extensive assessment of the interaction of bare and functionalized porous silica nanomaterials with RBCs concluded that SBA-15-type MSNs cause the deformation of RBCs and consequently lead to their disruption. Amine functionalizations on the surfaces of MSNs also reduce the hemolytic effect.…”
Section: Introductionmentioning
confidence: 99%
“…In the work published by Lin et al, the influence of a hydrophilic polymer shell (poly(ethylene glycol), PEG) was investigated by incubating the MSNPs in PBS and performing a silicomolybdic blue assay. It was found that nonpegylated MSNPs had greater degradation than pegylated MSNPs [12]. Moreover, Cauda et al reported that longer and denser PEG shells resulted in slower biodegradation kinetics [13].…”
Section: Introductionmentioning
confidence: 99%